Policies and Programs that Affect Ecosystem Health in the Wildland-Urban Interface - Terri Mashour; Martha C. Monroe (EDIS, 2009)
Revised! FOR201, a 9-page illustrated fact sheet by Terri Mashour and Martha C. Monroe, describes some policies, programs, and voluntary practices that influence natural resources or resource management at the federal, state, local, and neighborhood levels. Includes references. Published by the UF School of Forest Resources and Conservation, October 2008.